2011
DOI: 10.4028/www.scientific.net/amm.104.125
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Life Estimation under Cyclic Loading Including Out-of-Parallelism of the Characteristics

Abstract: The paper presents an algorithm of fatigue life determination for materials with no parallel fatigue characteristics under pure bending and pure torsion. The presented model uses the iteration method, and the applied fatigue criterion is function of the ratio of normal and shear stresses coming from bending and torsion, respectively. Three materials were applied for analysis: CuZn40Pb2 brass, 30CrNiMo8 medium-alloy steel and 35NCD16 high-alloy steel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The tests of fatigue life of specimens subjected to cyclic loadings were applied for determination of the parameters in the regression equation for pure bending according to the standard ASTM . The results of fatigue tests specimens made of brass under cyclic and block loading are presented respectively in papers . The authors also presented a model estimation the fatigue life under random load for specimens made of brass.…”
Section: Test Methodsmentioning
confidence: 99%
“…The tests of fatigue life of specimens subjected to cyclic loadings were applied for determination of the parameters in the regression equation for pure bending according to the standard ASTM . The results of fatigue tests specimens made of brass under cyclic and block loading are presented respectively in papers . The authors also presented a model estimation the fatigue life under random load for specimens made of brass.…”
Section: Test Methodsmentioning
confidence: 99%
“…These formulas can only be directly applied at the fatigue limit level or in the case of parallel characteristics. Otherwise, iterative methods should be used as presented in the papers [ 18 , 19 ].…”
Section: Multiaxial Strain Fatigue Criterion Using To the Concept mentioning
confidence: 99%
“…Figure 3 shows the moment of a crack's initiation due to fatigue, when the bending moment began to drop rapidly. An analysis of changes in the bending moment showed that greater bending moment amplitudes were obtained in the case of larger deviation amplitudes; thus, the fatigue life values were smaller [19]. This specific number of cycles was taken to be the number of cycles required to initiate a crack due to fatigue.…”
Section: Fatigue Testing Of 16mo3 Steel Under Tension-compression Andmentioning
confidence: 99%